Frontieres de la citoyennete et violence politique en Cote d'Ivoire - Ouedraogo, Jean-Bernard (Book collections on Project MUSE., 2008)
This book seeks to explain the events that have been taking place in C?te d'Ivoire since 1999 and which are commonly referred to as 'la crise ivoirienne' (the Ivorian crisis). It seems that the day to day interpretation of the events did not provide a satisfactory explanation of the deep fracture and that it was necessary to reconsider the essentialist theoretical categories that are striving to impose on us a false view, made cumbersome by ethnocentric prejudices. To avoid falling into the trap of the day to day interpretation of events will require an in-depth questioning of the causes of th.